The relationship between employee satisfactions, turnover intention and job security towards organizational change at Ranhill SAJ Sdn. Bhd - Hashim, Nurul Amalina (2019)
This research is conducted to study the relationship between employee satisfactions, turnover intention and job security towards organizational change at Ranhill SAJ Sdn. Bhd. while much research has been conducted on these three variables separately, very little has been done in terms of understanding the relationship between each of variables. This research aims to investigating the relationship between employee satisfactions, turnover intention and job security towards organizational change at Ranhill SAJ Sdn. Bhd. In obtaining employees opinion towards these issues, researcher has distributed 320 questionnaires to the respondents as the instrument for the collection of data. But, only 155 usable questionnaires were returned. Researcher used the Statistical Packages for Social Sciences (SPSS) version 25.0 software to analyze all data. Using SPSS, numerous tests were coverage such as reliability test, frequency distribution, descriptive analysis, Pearson’s correlation analysis and multiple regression analysis. The result shows that the relationship between employee satisfactions, turnover intention and job security are related towards organizational change.